Spatial and Temporal Variation in Groundwater Characteristics of the Coastal Regions of Tamil Nadu - Manikandan, K.; Natarajan, S.; Sivasamy, R.; Sankar, M.; Dadhwal, K. S. (Indian Forester, 2011)
This research work was aimed to study the spatial and temporal changes in groundwater quality of the coastal region of Cuddalore district, Tamil Nadu. The study was conducted during 2006 for which the coastal area was divided in to three zones based on 1.5 km spatial distance from sea. The groundwater was collected from 27 representative shallow wells for the whole year with three-month interval representing different seasons. The water samples collected were characterized for its chemical composition as well as electro-che mical properties. Based on the chemical composition, different quality parameters were arrived. The results revealed that 88 per cent of the wells recorded for slightly alkaline pH ranging from 7.6 to 7.9 with electrical conductivity varying froml.l to 4.0 dS m-1. The sodium and magnesium hazard was higher in most of the wells. Seawater intrusion is the key factor, which decides the quality of groundwater in this coastal zone. Natural rainfall is the next most important factor which balances the negative effects of seawater intrusion. In total, the grolIDdwater quality of this coastal zone was poor during swnm.er and optimum during monsoon and post monsoon seasons which necessitates that sufficient care may be taken when using this water for agricuJtura1/agroforestry/fOrestry/other land use purposes.